Movimentos sociais, mercado e internet: o ativismo gordo no Brasil - Lourenço, Bruna Scanavachi (Universidade Federal de São Carlos, 2022)
This study details the diffusion of critical ideas about fatness present in Fat Activism and Fat Studies in three main spaces: academic world, internet and markets. In order to understand how the narrative that fights fatphobia circulates through these spaces, the concepts of social space, everyday activism, and the process of incorporating the critique of social movements in the capitalist system are articulated in the academic field of critical studies of fat, in the social movement that fights fatphobia on the internet and in the collective narrative about fat in market spheres. Based on the premises of Economic Sociology, the mapping of the international context of the field of critical fat studies contextualizes Brazilian studies and identifies activism as part of the Fat Studies habitus; Brazilian activism on the social network Instagram shows itself as a type of everyday activism that targets culture and employs individualized actions that claim a fat identity as a form of resistance to the discriminatory narratives of fat; and finally, the relationship between companies and activists identifies the process of appropriation of activist discourses by capitalism as the gateway to the movement against fatphobia in the concept of organizational diversity, a dynamic that contributes to the legitimization of fatphobia as discrimination and shows progress in the transformation of the collective narrative of fat sought by the Fat Activism social movement and by Fat Studies. The context of critical fat studies was chosen given the emergence of addressing the gap between scientific evidence and misconceptions in the collective narrative about fat that supports weight stigma, narrative inconsistent with modern scientific knowledge that is just as harmful as racial and gender discrimination. This research offers contributions to the social movement when it highlights the social structure and the game that takes place between society and the narratives of fat, as well as for the critical academic space on fat, given the nascent stage of the Brazilian space that needs research interdisciplinary approaches that bring it closer to the international context and to the field of organizational research by highlighting the dynamics of appropriation of criticism by companies and its relationship with the concept of organizational diversity.

Este estudio detalla la difusión de las ideas críticas sobre la gordura presentes en Fat Activism y Fat Studies en tres espacios principales: el mundo académico, Internet y el mercado. Para entender cómo la narrativa que combate la gordofobia circula por estos espacios, se articulan los conceptos de espacio social, activismo cotidiano y el proceso de incorporación de la crítica a los movimientos sociales en el sistema capitalista en el campo académico de los estudios críticos de la gordura, en el social movimiento que lucha contra la gordofobia en internet y en la narrativa colectiva sobre la gordura en los ámbitos del mercado. Con base en las premisas de la Sociología Económica, el mapeo del contexto internacional del campo de los estudios críticos sobre el gordo contextualiza los estudios brasileños e identifica el activismo como parte del habitus de los Estudios sobre el gordo; El activismo brasileño en la red social Instagram se muestra como un tipo de activismo cotidiano que apunta a la cultura y emplea acciones individualizadas que reivindican una identidad gorda como una forma de resistencia a las narrativas discriminatorias de la gordura; y finalmente, la relación entre empresas y activistas identifica el proceso de apropiación de los discursos activistas por parte del capitalismo como puerta de entrada del movimiento contra la gordofobia en el concepto de diversidad organizacional, dinámica que contribuye a la legitimación de la gordofobia como discriminación y muestra avances en la transformación de la narrativa colectiva de la gordura buscada por el movimiento social Fat Activism y por el campo académico Fat Studies. El contexto de los estudios críticos de la grasa se eligió dado el surgimiento de combatir la brecha entre la evidencia científica y los conceptos erróneos en la narrativa colectiva sobre la grasa que sustenta el estigma del peso, una narrativa que es inconsistente con el conocimiento científico moderno, lo cual es tan dañino como la discriminación racial y de género. Esta investigación ofrece aportes al movimiento social cuando destaca la estructura social y el juego que se da entre la sociedad y las narrativas de la gordura, así como para el espacio académico crítico sobre la gordura, dada la etapa embrionaria del espacio brasileño que necesita investigaciones interdisciplinarias que lo acerquen al contexto internacional y para el campo de la investigación organizacional al destacar la dinámica de apropiación de la crítica por parte de las empresas y su relación con el concepto de diversidad organizacional.
Social movements, market and internet: fat activism in Brazil
Movimientos sociales, mercado e internet: activismo gordo en Brasil
Keywords: Ativismo gordo; Gordofobia; Diversidade organizacional; Fat studies; Fat activism; Diversity; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO